2017
DOI: 10.1007/s12678-017-0435-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation of the Hydrogen Evolution Reaction on Electrodeposited Films of Cr(OH)3 and Cr2O3 in Mild Alkaline Solutions

Abstract: The hydrogen evolution reaction (HER) from water reduction is the main cathodic reaction in the sodium chlorate process. The reaction typically takes place on electrodes covered with a Cr(III) oxide-like film formed in situ by reduction of sodium dichromate in order to avoid reduction of hypochlorite and thereby increase the selectivity for the HER. However, the chemical structure of the Cr(III) oxide-like film is still under debate. In the present work, the kinetics of the HER were studied using titanium elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
5
15
0
Order By: Relevance
“…The result in Figure 10, in which α ranges from 0.4 through 0.6, are therefore quite reasonable. Similar observations with fractional reaction order have been made for other electrocatalysts for both the hydrogen evolution reaction 14,40,50,51 and the oxygen evolution reaction. 48,49,[52][53][54] The experimental values of Tafel slope in Tables IV and V 44 This may be related to similarities in the state of surface Ni in the oxides and metal when exposed to the ambient air or water.…”
Section: Resultssupporting
confidence: 82%
“…The result in Figure 10, in which α ranges from 0.4 through 0.6, are therefore quite reasonable. Similar observations with fractional reaction order have been made for other electrocatalysts for both the hydrogen evolution reaction 14,40,50,51 and the oxygen evolution reaction. 48,49,[52][53][54] The experimental values of Tafel slope in Tables IV and V 44 This may be related to similarities in the state of surface Ni in the oxides and metal when exposed to the ambient air or water.…”
Section: Resultssupporting
confidence: 82%
“…Based on the EDX analysis, a Cr:O ratio of 1:0.75 was obtained for Cr(OH) 3 @Au, which is clearly smaller than the Cr:O ratio of 1:3 expected for Cr(OH) 3 . Metallic Cr has been detected after electrodeposition of Cr(OH) 3 ,, and the interpretation is that Cr metal is formed together with the hydroxide or oxide. XRD was used to detect the presence of metallic Cr, but the diffractograms showed only peaks related to the substrate (Figure S2).…”
Section: Resultsmentioning
confidence: 87%
“…By increasing the laser power to 0.35 mW, clear signals from the deposited layer could observed, Figure a, with signatures from both Cr(OH) 3 and Cr 2 O 3 . In a recent paper, it was shown that for Cr(OH) 3 @Ti no conversion to the oxide takes place below 0.7 mW . By further increasing the laser power, conversion from Cr(OH) 3 to crystalline Cr 2 O 3 takes place, Figure b, as also shown previously ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations